Effects of preheating and drying methods on pyridoxine, phenolic compounds, ginkgolic acids, and antioxidant capacity of Ginkgo biloba nuts. Issue 9 (9th August 2021) - Amoussa, Abdou Madjid Olatounde; Zhang, Lixia; Lagnika, Camel; Riaz, Asad; Zhang, Liuquan; Liu, Xianjin; Beta, Trust
Abstract : Abstract: Although ginkgo nuts are very nutritious and loaded with numerous bioactive compounds, the nuts contain significant levels of unwanted compounds (ginkolic acids) which are toxic to consumption. To reduce or eliminate these toxic compounds without impacting the nutritional value and the bioactivity of the final product, an appropriate processing technology is needed. Thus, the effect of preheating (90 and 120°C) prior to drying (freeze drying: FD, hot air drying: HAD, and HAD in tandem with FD: HAD‐FD) was evaluated on ginkgolic acids, pyridoxine analogues, phenolic compounds, and antioxidant properties of ginkgo nuts. Our results pointed out a significant decrease (below 50%) of ginkgolic acids in ginkgo nuts samples processed at 90°C compared to the control. The major compounds found after treatments were respectively, kaempferol (36.66‐354.38 µg/g), quercetin (9.04‐183.71 µg/g), and caffeic acid (19.66‐106.88 µg/g). Principal component analysis (PCA) revealed that preheating at 90°C prior to HAD‐FD would be a proper and reasonable approach for preserving the bioactive compounds and antioxidant capacity of ginkgo nuts (EC50 ranged from 2.25 to 4.60 mg/mL) while significantly reducing their content in toxic compounds.